STUDY ON THE HISTORICAL AND LITERARY CONTEXT OF THE MEDIEVAL ENGLISH - Sonam Kamboj (International journal of economic perspectives, 2022)
In the history of English literature, the transition from Greek to medieval philosophy, which theorized on religion, nature, metaphysics, human beings, and society, was a difficult one. Even though the literature of this period represented stronger religious values, the love-hate connection between medievalphilosophy, which was mostly founded on Christianity, with Greek civilization was evident. The ideals of this period are continued in present philosophical ideologies. The paper provides a theatrical overview of the major aspects of medieval English. It is impossible to comprehend present philosophical concerns without first grasping the philosophical issues of this era. During this period, the catholic tradition as well as Protestantism, a religious reform movement against the church, wasorganized. Philosophy and theoretical views associated with Christianity were well-organized during the Medieval Period, and philosophy, science, and theoretical thoughts all supported religion.